Intensifikasi Produk “Petani Hidroponik” dalam Integrasi Aquaponik di Yayasan Al Anshar Timor Timur, Makassar, Sulawesi Selatan - Mubarak, Fhahri; Khairuddin, Khairuddin; Awaluddin, Sri Prilmayanti; Azis, Siti Yuki Oktafitriah; Reski , Reski; Padang, Dirgaraya Kala’ (Penerbit Goodwood, 2025)
Purpose: To help the partner ‘Moreira Farm’ to solve the problem of efficient and effective hydroponic plant management and quality. Methodology: carried out at Moreira Farm in the Al Anshar East Timor Islamic Boarding School area, the method of applying innovation by increasing the quantity and quality of hydroponics by providing technological tools and innovations to streamline and increase the yield of hydroponic plants so that they are of higher quality than before. Results: the addition of innovation technology tools increases the results of hydroponic management with better quality. Community service has been carried out by involving partners Moreira Farm Pondok Pesantren Al Anshar East Timor by providing assistance in the form of innovation technology tools and materials. Conclusions: Moreira Farm Partnert experienced significant improvements and increases in hydroponic crop yields. Limitations: This service is limited to land conditions that still need to be revitalised. Contribution: This service is useful in the agricultural sector, namely Hydroponics, Aquaponics and Nutrient Film Technique.